Fiscal Constraints of a Fixed Exchange Rate Regime. (IMF Working Papers; Working Paper ;, 1989)
The paper considers whether the implementation of a fixed exchange rate regime requires or implies binding constraints on fiscal policy. The main conclusions are that, from a country perspective, the effective constraint is on the degree of monetary financing, which bears an uncertain relationship to the size of the budget deficit; that, from a systemic perspective, the financial stability of the currency area can be ensured by making the monetary and fiscal authorities independent of one another; and that the case for coordination of fiscal policies-whatever its merits-is not enhanced by the creation of a fixed exchange rate regime.